Social constructions of racial images in introductory criminal justice and criminology textbooks: a content analysis. Issue 6 (2nd November 2021) - Park, Seong-Min; Kim, Jeong L.; Park, Hyoungah; Kim, Yongsok; Cuadrado, Mary
ABSTRACT: Visual images in introductory textbooks play an important role in constructing the concept of race for students entering the field of criminal justice/criminology. Prior studies on race depictions in criminal justice/criminology textbooks have focused on individual images depicting persons as criminal justice personnel, relating to type of crime or criminal justice context, and as victim. By analyzing a total of 2, 286 individuals in 1, 943 images from 23 textbooks this study expands on this approach by also differentiating exclusive portrayals from social compositions (two or more individuals), analyzing placement of image within substantive area of the text, and by examining interactive depictions (victim/criminal, professional/criminal, and victim/professional) according to race. The results reveal noteworthy racially biased depictions in introductory criminal justice/criminology textbooks.